What Happened on July 21st: An Investigation of Trauma and Trigger Warnings in the English Classroom. Issue 2 (3rd April 2019) - Wolfsdorf, Adam; Scott, Alison; Herzog, Sarah
ABSTRACT: The controversy surrounding trigger warnings has highlighted a mystifying confound in post-secondary education. Faculty, students and school bureaucracies are divided. While trigger warning proponents emphasise the value of protecting students with trauma histories from unscaffolded exposure to content related to sexuality, violence, race and political strife, agonists interpret the trigger warning as a threat to academic freedom, artistry and professor autonomy. This paper presents an episode that occurred at a prominent school of education, in which an instructor's choice of content triggered a post-traumatic response in a student. As the story unfolds, the narrative shifts back and forth between the instructor's and the student's experience of the event. The piece concludes with a commentary made by a clinical psychologist and trauma expert, who weighs in on the challenges confronting both professors and students, as each attempts to navigate handling emotionally charged, potentially triggering contents in the post-secondary classroom.